Assessing the efficacy of coherent anti‐Stokes Raman scattering microscopy for the detection of infiltrating glioblastoma in fresh brain samples. Issue 3 (11th March 2016) - Galli, Roberta; Uckermann, Ortrud; Temme, Achim; Leipnitz, Elke; Meinhardt, Matthias; Koch, Edmund; Schackert, Gabriele; Steiner, Gerald; Kirsch, Matthias
Abstract : Coherent anti‐Stokes Raman scattering (CARS) microscopy is an emerging technique for identification of brain tumors. However, tumor identification by CARS microscopy on bulk samples and in vivo has been so far verified retrospectively on histological sections, which only provide a gross reference for the interpretation of CARS images without matching at cellular level. Therefore, fluorescent labels were exploited for direct assessment of the interpretation of CARS images of solid and infiltrative tumors. Glioblastoma cells expressing green fluorescent protein (GFP) were used for induction of tumors in mice ( n = 7). The neoplastic nature of cells imaged by CARS microscopy was unequivocally verified by addressing two‐photon fluorescence of GFP on fresh brain slices and in vivo . In fresh unfixed biopsies of human glioblastoma ( n = 10), the fluorescence of 5‐aminolevulinic acid‐induced protoporphyrin IX was used for identification of tumorous tissue. Distinctive morphological features of glioblastoma cells, i.e. larger nuclei, evident nuclear membrane and nucleolus, were identified in the CARS images of both mouse and human brain tumors. This approach demonstrates that the chemical contrast provided by CARS allows the localization of infiltrating tumor cells in fresh tissue and that the cell morphology in CARS images is useful for tumor recognition.Experimental glioblastoma expressing green fluorescent protein. Abstract : Typical feature of malignant brain tumors are infiltrating neoplastic cells, and their intraoperative detection would constitute a key prognostic feature. CARS microscopy is a label‐free, non‐invasive optical technique that offers the potential to visualize the tumor in situ and could therefore complement the existing intraoperative imaging tools. The morphochemistry of cells retrieved by CARS microscopy enables to discern the tumor from the surrounding normal brain tissue, thereby providing great potential towards tumor resection optimization.